Patrons, Painters, Women In Distress: The Changing Fortunes of Nevʿizade Atayi and Üskübi Mehmed Efendi in Early Eighteenth-Century Istanbul - Artan, Tülay (Muqarnas, 2022)
Images of Ottoman women in verse and manuscript painting that have long been interpreted as realistic representations of their everyday life stand in stark contrast with how women are represented, addressed, and pigeonholed in religious books of conduct. While no distinction is made between the elite and commoners in these depictions of pleasurable outdoor activities, the regular, routine roles that the women played in the family and society disappear from sight. In light of a rare but well-known court scene showing women in public space and at a real trial of 1582, appended in all illustrated copies of Nevʿizade Atayi’s Ḫamse, I discuss the specifics of the legal opinion with which Pir Mehmed Efendi was associated, and how the trial was recollected in Istanbul’s literate circles after more than a century. Whether the production of the five illustrated Ḫamses in the first quarter of the eighteenth century was a concerted effort on the part of a specific group of artists, both Istanbulites and Inner Asians, is discussed in the second part of the article.